Sports Management Events On The Social Cultural Phenomenon of The Tambakromo Village, Pati Regency (Journal of Physical Education and Sports, 2019)
This research aims to study and analyze. The social cultural phenomena of the Tambakromo people before and after they succeeded in overseas areas. The role of youth and the community of Tambakromo Village in organizing sports events. The social cultural phenomenon of the Tambakromo Village community with a sports event held by the youth and Tambakromo Village community. This research is a qualitative research with a case study approach. Data collection techniques are interviews, observation, and documentation. The validity of the data uses source triangulation. The results of this study are that here are striking differences in the lives of the Tambakromo people before and after success in the overseas areas. The sporting event was initiated by the youth and the people of Tambakromo Village who had concerns about sports activities in 2008. There were social cultural phenomena in the Tambakromo community after the holding of the sport event. The first phenomenon is the problem of fundraising, the second phenomenon is motivation in sports activities and the third phenomenon is social harmony.